Organizing farmers for effective training and capacitation for tree-based enterprises - Gassner, A.; Torres, A.G.; Wardell, D.A.; Duque-Piñon, C. (World Agroforestry Centre, 2021)
Since the adoption of a nationwide community-based forest management strategy 25 years ago, people’s organizations (POs) have been the Philippine Government’s key partners in programs and projects in upland communities, including the Natural Resources Management Program (NRMP), the Environment and Natural Resources Sectoral Adjustment Loan Program (ENR-SECAL), and the Community-Based Resource Management Program (CBRMP). These programs have provided important lessons that have served as the foundation for recent Government initiatives. In 2018, a PO accreditation system was pioneered through the Integrated Natural Resources and Environmental Management Project (INREMP). This innovative mechanism to improve disbursement and increase POs’ capacity to facilitate high-quality sub-projects has, however, been confronted with implementation challenges. This brief suggests concrete actions to increase the capacity of the Department of Environment and Natural Resources (DENR) and POs and to simplify the complex process for POs to support their transformation into small, community-based enterprises.